1976
DOI: 10.1007/bf00036990
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stress intensity factors for arresting cracks in DCB specimens

Abstract: Crack arrest toughness Kla values are usually evaluated using a static stress intensity factor analysis. According to this procedure which is advocated by Crosley and Ripling [i], the process of crack arrest is treated as mathematically identical to the process of crack initiation, with only the time scale being reversed. Dynamic effects (stress waves, structural vibrations) and their possible influence on the process of crack arrest are not considered. This concept is contested by Hahn et al. [2]. These autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 1 publication
2
23
0
Order By: Relevance
“…In order to investigate the influence of dynamic effects on the mechanical behavior of cracks at arrest, the stress condition at the tip of a propagating and subsequently arresting crack was analyzed [10][11][12][13][14]. Using the epoxy resin Araldite B, the actual dynamic stress intensity factors, Kp yn, were measured by means of the shadow optical method of caustics in transmission.…”
Section: Influences Of Dynamic Effectsmentioning
confidence: 99%
“…In order to investigate the influence of dynamic effects on the mechanical behavior of cracks at arrest, the stress condition at the tip of a propagating and subsequently arresting crack was analyzed [10][11][12][13][14]. Using the epoxy resin Araldite B, the actual dynamic stress intensity factors, Kp yn, were measured by means of the shadow optical method of caustics in transmission.…”
Section: Influences Of Dynamic Effectsmentioning
confidence: 99%
“…and that this is equal to nΓ, being a dimensionless coefficient accounting for some initial bluntness of the crack tip then, Equation (17) can be reduced to find the equilibrium point of crack arrest length at = = 0 to approximately be [28,29]:…”
Section: Steady-state Dcb Analytical Solutionmentioning
confidence: 99%
“…The impact three-point bending test using elastic bars is possible to evaluate the deformation and fracture behavior of materials with accuracy as well as achievement of higher loading rate than that of Charpy impact test. On the other hand, it is reported that there is great possibility of in uence of inertial force on experimental results of the above-mentioned impact fracture tests 14) . For evaluation of the impact fracture properties of materials while taking effects of inertial force into consideration, application of several fracture mechanical parameters were proposed 15,16) .…”
Section: Introductionmentioning
confidence: 99%